VD_FINDINFO HC / 2011 / 396 vom 28. Juli 2011 - VD Tribunal cantonal (2011)
PROTECTION DE L'UNION CONJUGALE, OBLIGATION D'ENTRETIEN, CONJOINT | 24 al. 1 CC, 148 CPC (CH), 308 al. 1 let. b CPC (CH), 308 al. 2 CPC (CH), 312 al. 1 CPC (CH)